In memoriam Zdeněk F. Oliverius - Clarke, Jonathan E. M. (Specimina philologiae Slavicae, 1985)
The Bibliography in this publication presents Oliverius as one of the most versatile scholars in the field of Russian linguistics. With no difficulty one can trace here the imprint of his four brief years in Australia between December 1968, and September 1972. Here he was one of the first scholars in Russian studies of truly high calibre, with a unique international reputation. And yet as the first President of the Australian and New Zealand Slavists' Association he was realistic enough not to impose on the local scene a standard model usual on other continents and involving a wide range of Slavic languages. The purpose o f this volume is to focus attention on Oliverius's scholarly activities in this country, reviewing their climax during the period from 1969 to 1972 as well as the prelude and aftermath during his Prague years. This publication, in which six Slavists from both Melbourne departments have taken part, is the first publication attempting to examine the roots and sources of Slavic studies in Australia.